2011
DOI: 10.1038/onc.2010.582
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide screen reveals WNT11, a non-canonical WNT gene, as a direct target of ETS transcription factor ERG

Abstract: E26 transforming sequence-related gene (ERG) is a transcription factor involved in normal hematopoiesis and is dysregulated in leukemia. ERG mRNA overexpression was associated with poor prognosis in a subset of patients with T-cell acute lymphoblastic leukemia (T-ALL) and acute myeloid leukemia (AML). Herein, a genome-wide screen of ERG target genes was conducted by chromatin immunoprecipitation-on-chip (ChIP-chip) in Jurkat cells. In this screen, 342 significant annotated genes were derived from this global a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(40 citation statements)
references
References 51 publications
1
39
0
Order By: Relevance
“…Activation of ERG expression by TMPRSS2:ERG gene fusion results in aberrant activation of different signalling cascades in ERG fusion-positive as compared with ERG fusion-negative prostate cancers 27 32–34. One of the best known consequences of ERG expression is activation of WNT signalling26 27 35 It is tempting to speculate that FOXP2 and ERG, or their target genes, interfere with pathways governing tumour aggressiveness, possibly including the WNT pathway, which is subsequently reflected by the different clinical course in ERG-positive and ERG-negative cancers. The genes or mechanisms mediating this effect remain to be identified.…”
Section: Discussionmentioning
confidence: 99%
“…Activation of ERG expression by TMPRSS2:ERG gene fusion results in aberrant activation of different signalling cascades in ERG fusion-positive as compared with ERG fusion-negative prostate cancers 27 32–34. One of the best known consequences of ERG expression is activation of WNT signalling26 27 35 It is tempting to speculate that FOXP2 and ERG, or their target genes, interfere with pathways governing tumour aggressiveness, possibly including the WNT pathway, which is subsequently reflected by the different clinical course in ERG-positive and ERG-negative cancers. The genes or mechanisms mediating this effect remain to be identified.…”
Section: Discussionmentioning
confidence: 99%
“…There is also little information on downstream targets of ERG that contribute to malignant leukemogenesis. A genome wide screen of ERG target genes conducted with ChIP-chip in Jurkat cells included the WNT signaling genes WNT11, WNT2, WNT9A, CCND1 , and FZD7 (Mochmann et al, 2011). Sampling of patient diagnostic material showed that ERG and WNT1 were co-expressed in 80% of AML, whereas knockdown of ERG1 by siRNA lead to WNT1 transcript down-regulation and WNT1 transcripts could be stimulated with tet-on ERG inducible assay.…”
Section: B Mechanisms Of Ets Protein Mediated Oncogenesismentioning
confidence: 99%
“…7, 12 Deregulation of the WNT pathway has been linked to leukemogenesis in T-ALL. 13, 14 The previously unreported FAT1 mutation rate of 15% in adult T-ALL stresses the importance of the WNT pathway in T-ALL.…”
mentioning
confidence: 99%